Evaluating the EMS and EMU Using Stochastic Simulations : Some Issues - Masson, Paul (IMF Working Papers; Working Paper ;, 1993)
Evaluations of European monetary integration using model simulations have given conflicting results, and the paper attempts to elucidate the reasons for the differences. Several features stand out: how to model realignments; how monetary policy is set for individual countries or for Europe; and how large are risk premium shocks in exchange markets. We quantify the effects of different assumptions relating to these features using MULTIMOD.